Re-industrialization and Digital Finance: Synergy of Advanced Technology in Driving National Economic Growth in Indonesia (Architecture Image Studies, 2025)
The development of advanced technology and financial digitalization has become a major factor in the reindustrialization process in various developed countries, such as the United States, Japan, and China. In Indonesia, this condition is studied to increase national economic competitiveness and encourage sustainable economic growth. This research aims to analyze the synergy between the process of reindustrialization and digital financial innovation in Indonesia, as well as its impact on national economic growth. Through quantitative methods and literature review, this study reveals that the application of technologies such as artificial intelligence, blockchain, and the Internet of Things (IoT) is able to strengthen digital financial infrastructure, improve the efficiency of financial services, and expand financial inclusion at all levels of society. In addition, the analysis highlights the importance of innovative policies and adaptive regulations in accelerating technology adoption while ensuring consumer protection and financial system stability. The results of the study show that the synergy between reindustrialization and digital finance can strengthen the national industrial sector, increase global competitiveness, and support inclusive and sustainable economic growth in Indonesia. Therefore, cross-sector collaboration, policy innovation, and thedevelopment of a conducive digital ecosystem are the main keys in utilizing the potential of advanced technology for national economic development.